Perceptions of the prevalence of cigarette smoking by peers: A study of Taiwanese, Filipino, and Thai high school students - Randy M. Page (2018)
Youth cigarette smoking is a major public health concern in Southeast Asia. A suspected determinant of youth smoking is perceived peer behavior. Previous research has suggested that the probability that a teenager will use substances increases when there is the perception that most peers engage in the substance use behavior. This study aimed to assess the perceptions of the prevalence of peer cigarette smoking in samples of high school students from three Southeast Asian countries and to examine the association of these perceptions to self-reported personal use of cigarettes. Perceptions of the prevalence of peer smoking were generally characterized by the perception that most students do not smoke. However, a significant percentage of students held the perception that most students were current smokers. Students who held this perception were at increased risk of being current smokers relative to those who believed most students were not current smokers. The results of this study imply that public health programs may benefit from health promotion interventions which focus on dispelling misconceptions that most youth smoke cigarettes.